INVESTIGASI EMPIRIS TERHADAP PERILAKU FREENDING DALAM REAKSI PASAR TERHADAP PUBLIKASI LABA GOOD NEWS DAN BAD NEWS - Andreas Lako (Jurnal Riset Akuntansi dan Keuangan, 2005)
This study purposes to investigate the free-riding behattior from stoek market actors in responding to the good and bad news earnings announcements. Theoreticolly, free-riding (and externality) behaviors are the source of market failure, which suggest that regulotion mry still be needed (Wolk et al. 2001; Scott, 2003). But, the empirical investigation with respect to the issue is still rare. Using the good and bad news earnings announcements of 1998-2000 from LQ45 firms listed at theJakarta Stock Exchange and a quasi-experimental design, the results show that there arefree-riding behaviorsfrom market actors in responding to the good news earnings announcements from treatment sample. However, this study fails to find the free-riding behaviors from market actors in responding to the bad news earnings onnouncernents. The study also finds a number of phenomena that reflected the market anomaly. For thefuture research, this study suggests to extend the samples ond periods of earnings announcements, as well as appty the theory and models of behavioral finance.Kata kunci: free-riding, good news, bad news, quasi experimentol, treafinent sample dut contrul sample.